2020
DOI: 10.33160/yam.2020.08.009
|View full text |Cite|
|
Sign up to set email alerts
|

Pemafibrate Dramatically Ameliorated the Values of Liver Function Tests and Fibrosis Marker in Patients with Non-Alcoholic Fatty Liver Disease

Abstract: Background Non-alcoholic fatty liver disease ( NA FLD) is a ch ronic liver disease related to metabolic syndrome, which can progress to liver cirrhosis. Standard medication has not been established. Pemafibrate is a selective peroxisome proliferatoractivated receptor (PPAR) α modulator. We retrospectively evaluated the efficacy of pemafibrate in patients with NAFLD. Methods We retrospectively enrolled 17 patients (ten men, seven women; median age, 63 years; range, 27-81 years). They were all proven to have fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
4
14
2
Order By: Relevance
“…Pemafibrate was also reported to significantly reduce alanine aminotransferase (ALT) and γ‐glutamyl transpeptidase (γ‐GTP) 11 . Recent studies have reported the efficacy and safety of pemafibrate for patients with NAFLD 12–14 . We also revealed the efficacy and safety of pemafibrate for biopsy‐proven NASH patients 15 .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Pemafibrate was also reported to significantly reduce alanine aminotransferase (ALT) and γ‐glutamyl transpeptidase (γ‐GTP) 11 . Recent studies have reported the efficacy and safety of pemafibrate for patients with NAFLD 12–14 . We also revealed the efficacy and safety of pemafibrate for biopsy‐proven NASH patients 15 .…”
Section: Introductionmentioning
confidence: 76%
“… 11 Recent studies have reported the efficacy and safety of pemafibrate for patients with NAFLD. 12 , 13 , 14 We also revealed the efficacy and safety of pemafibrate for biopsy‐proven NASH patients. 15 Although the study population was small and the duration of treatment was short in these previous studies, pemafibrate is expected to be a promising treatment for NAFLD patients with hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 76%
“…There are some advantages to this study. First, the treatment period with pemafibrate on NAFLD in this study is longer than in past studies, which had 12-24 weeks of follow-up [ 6 , 7 ]. Second, no patients with diabetes were included.…”
Section: Discussionmentioning
confidence: 94%
“…We previously reported the short-term outcomes of patients with NAFLD treated with pemafibrate that showed significant improvement in markers of hepatic inflammation and function at three months [ 5 ]. Existing studies reporting the effects of pemafibrate in patients with NAFLD are limited to short-term outcomes [ 6 , 7 ]. There are no reports of long-term outcomes in the literature at this time.…”
Section: Introductionmentioning
confidence: 99%
“…A single-arm prospective study reported by Seko et al ( 22 ) showed that the levels of transaminase, γ-GTP and fasting TG at baseline were significantly reduced and that HDL cholesterol and the platelet count were significantly elevated in comparison to the values at 12 weeks in 20 patients with NAFLD. Another retrospective study ( 23 ) showed that the transaminase and γ-GTP levels were decreased in patients with fatty liver disease who were treated with pemafibrate. The results of the previous studies were considered to be consistent with the present results.…”
Section: Discussionmentioning
confidence: 99%